Optical viscous quantum ferromagnetic model for thermal radiation - Körpınar, Talat; Körpınar, Zeliha (Springer, 2023)
In this article, optical recursional viscous ferromagnetic microfluidics normalized Delta(tau), D(nu), Delta(beta) bilayered viscous ferromagnetic microbeam solidity are described in de Sitter space. Thus, we obtain hydromagnetic recursional viscous ferromagnetic microfluidics normalized thermal Delta(tau), Delta(nu), Delta(beta) radiation. Also, we have thermal viscous ferromagnetic conducting of Delta(tau), Delta(nu), Delta(beta) bilayered microbeam. Moreover, we demonstrate viscous ferromagnetic phase of heat transport for nanofluid recursional microfluidics normalized thermal Delta(tau), Delta(nu), Delta(beta) radiation in de Sitter space. Finally, we get optical thermal stimulation for microstructured nanofluid recursional microfluidics normalized thermal Delta(tau), Delta(nu), Delta(beta) radiation are constructed by numerical results.
Keywords: Ferromagnetic Microfluidics; Flexible Inextensibility; Hydromagnetic Model; Thermal Radiation; Heat-Transfer; Entropy Generation; Solar Collector; Fluid-Flow; Performance; Nanofluids